The immune response to resistance exercise - Simonson, S. R. (The Journal of Strength and Conditioning Research, 2001)
The immune response to exercise has received increased attention in the last decade. Most of this attention has focused on aerobic exercise (AEX), whereas the effect of resistance exercise (REX) has received comparatively little notice. Resistance exercise and AEX have different physiologic impacts; perhaps this also applies to the immune system. The purpose of this review was to determine a consensus from the REX immune studies that have been completed. This is complicated by the multitude of immune parameters, the varying methods used to assess them, and the paucity of studies performed. Thus, it is difficult to make a blanket statement. There is a REX-induced leukocytosis. Resistance conditioning (RCO) does not alter this response or affect the resting immune system. From these data, it appears that neither REX nor RCO demonstrates a significant impact on peripheral immunosurveillance.